Bluetongue in white-tailed deer (Odocoileus virginianus) in Northeastern Mexico - Martínez-Burnes, Julio; Barrios-García, Hugo; Alva-Pérez, Jorge; Ramírez-Romero, Rafael; García-Márquez, Luis J.; López-Mayagoitia, Alfonso (Brazilian Journal of Veterinary Pathology, 2017)
Bluetongue (BT) and epizootic hemorrhagic disease of deer (EHD) are two distinct viral hemorrhagic diseases of domestic and wild ruminants caused by members of the family Reoviridae and transmitted by Culicoides midges. These conditions have been recognized in Canada and the United States for many years, but not in Mexico. Although in Mexico there is serologic evidence of EHD virus (EHDV) and bluetongue virus (BTV) in domestic and wild ruminants, to our knowledge, there have never been reports of clinical illness or fatalities attributed to either of these viruses. Two free ranging white-tailed deer (Odocoileus virginianus) in two licensed hunting ranches in Northern Mexico near the Texas border died unexpectedly. Postmortem and microscopic examinations revealed hemorrhagic lesions compatible with viral hemorrhagic disease (Reoviridae: Orbivirus). Tissues from one animal tested positive by RT-PCR for BTV but negative for EHDV. To our knowledge, this is the first time in Mexico where deer dying with hemorrhagic lesions consistent with Bluetongue tested positive for BTV by PCR.